Using Multiple Representations in Chemical Kinetics: Relationship Between Graphs and Texts - Chandrasegaran, Arulsingam; Tan, K.; Treagust, David; Mocerino, Mauro (SEAMEO RECSAM, 2011)
A quantitative case study design involving 1,216 Singapore students in grades 10 – 12 was used to evaluate their ability to relate the graphical representations of kinetics of acid reactions with written texts using the Acid Reactions Instrument consisting of 12 items classified into four reaction groups. The Cronbach’s alpha reliability for the 12 items was found to be 0.82. Students’ understanding of graphical representations in each reaction group was indicated by correct responses ranging from 57% to 82.3%. Their ability to relate the graphical representations to the corresponding textual representations in each reaction group was indicated by correct responses ranging from 47.2% to 73.7%. These differences were statistically significant for all four reaction groups. As students advanced in their studies from secondary school to junior college, they demonstrated greater proficiency in their understanding of multiple external representations as well in their ability to relate between representational systems.